Study of Forest Types, Inventory of Tree, and Chlorofil Contents of Malabar Forest Leaves, Malang City - Roimil Latifa; Endrik Nurrohman; Samsun hadi (UNIVERSITAS NEGERI PADANG, 2021)
This research aims to examine the forest types, inventory of tree species, and chlorophyll content of plant leaves in the Malabar forest, Malang City. This type of research is descriptive quantitative. This research was done from the month of August to December 2020 and took place in Malabar Forest and Biology Laboratory of University of Muhammadiyah Malang. Data collection methods using exploratory techniques and laboratory observations. Data analysis is done by descriptive quantitative. The results showed that 101 tree species inhabit Malabar forest with the most Tanjung trees with 175, and the least number is Srikaya with only one tree. Malabar forest is classified as a forest with a spreading form. In the dry season, the average chlorophyll ‘a’ content of leaves was highest in starfruit leaves (35.848 µg/ml), the lowest average of starfruit leaves (17.857µg/ml), the average chlorophyll ‘b’ content of leaves was highest in Tabebuya leaves (58.862µg/ml). The lowest was Norfolk Pine leaf (9,124 µg/ml), the highest total leaf chlorophyll was Tabebuya leaf (91,737µg/ml), and the lowest was the Norfolk Pine leaf (28,517µg/ml). In the rainy season, the highest chlorophyll ‘a’ content was Sengon tree (34.3µg/ml) and the lowest was Chocolate (0.3µg/ml), the highest chlorophyll ‘b’ was Genitu (131.6µg/ml) the lowest was Lamtoro (6.5µg/ml), the highest total chlorophyll was Melinjo (90.7µg/ml) and the lowest was Kol Banda (3.3µg/ml). Keywords: Malabar Forest, Inventory, Leaf Chlorophyll.